In vitro assessment of aspalathin-enriched Rooibos (Aspalathus linearis) extract treatment in statin-induced hepatotoxicity - Millar, Danielle Ann (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.